Asteraceae as a model system for evolutionary studies: from fossils to genomes - Palazzesi, Luis; Pellicer, Jaume; Barreda, Viviana Dora; Loeuille, Benoît; Mandel, Jennifer R.; Pokorny, Lisa; Siniscalchi, Carolina M.; Tellería, María Cristina; Leitch, Ilia J.; Hidalgo, Oriane (Botanical Journal of the Linnean Society)
With c. 24 700 species (10% of all flowering plants), Asteraceae are one of the largest and most phenotypically diverse angiosperm families, with considerable economic and ecological importance. Asteraceae are distributed worldwide, from nearly polar latitudes all the way to the tropics, and occur across a diverse range of habitats from extreme deserts to swamps and from lowland rainforests to alpine tundra. Altogether, these characteristics make this family an outstanding model system to address a broad range of eco-evolutionary questions. In this review, we summarize recent progress in our understanding of Asteraceae on the basis of joint efforts by specialists in the fields of palaeobotany, cytogenetics, comparative genomics and phylogenomics. We will highlight how these developments are opening up new possibilities for integrating fields and better comprehending evolution beyond Asteraceae. Fil: Palazzesi, Luis. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Pellicer, Jaume. Royal Botanic Gardens; Reino Unido Fil: Barreda, Viviana Dora. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Loeuille, Benoît. Royal Botanic Gardens; Reino Unido Fil: Mandel, Jennifer R. University of Memphis; Estados Unidos Fil: Pokorny, Lisa. Royal Botanic Gardens; Reino Unido Fil: Siniscalchi, Carolina M. Mississippi State University.; Estados Unidos Fil: Tellería, María Cristina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Laboratorio de Sistemática y Biología Evolutiva; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina Fil: Leitch, Ilia J. Royal Botanic Gardens; Reino Unido Fil: Hidalgo, Oriane. Royal Botanic ...